Peran Lembaga PAUD dalam Penanaman Nilai-nilai Moderasi Beragama bagi Anak Usia Dini di Kecamatan Air Periukan Kabupaten Seluma Bengkulu - Andani, Fidhia; Asengki, Asengki; Meysarah, Meysarah; Liska, Titin Haji (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to describe the role of early childhood education (PAUD) institutions in instilling religious moderation values ​​in early-age students. This study uses a field research type in Mutiara Bunda PAUD, Witri State Kindergarten, Harapan Bangsa PAUD, Kusuma Wangi PAUD and Tarbiyatul Atfal PAUD, Air Periukan District, Seluma Regency, Bengkulu. The targets of this study were school principals, teachers, and education personnel. The results of the study indicate that the role of PAUD principals in decision-making is carried out through discussion; providing innovation by initiating school programs; providing motivation to teachers and students; and providing rewards. The role of teachers consists of motivating by telling stories; reminding the 5S motto, using Indonesian in schools; managing the learning environment; providing rewards; and guiding moderate attitudes. The role of educators consists of managing student admissions; preparing administration books, school programs, teacher training programs; and evaluating educational development and coaching activities in instilling religious moderation values ​​in children in schools.